2017
DOI: 10.22373/psikoislamedia.v2i1.1822
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Spiritualitas Terhadap Resiliensi Pada Mahasiswa Yang Sedang Mengerjakan Skripsi

Abstract: ABSTRAKMahasiswa yang sedang mengerjakan skripsi diperkirakan akan menghadapi tekanan yang lebih berat dibandingkan mahasiswa pada umumnya yang berasal dari faktor internal maupun eksternal.Faktor internal meliputi rasa malas, motivasi rendah, takut bertemu dosen pembimbing, sulit menyesuaikan dosen pembimbing.Faktor eksternal meliputi, minimnya waktu bimbingan, kesulitan dalam hal mencari tema, judul, alat ukur yang digunakan, kesulitan mendapatkan referensi dan lain-lain.Jika mahasiswa tidak bisa beradaptasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 1 publication
2
6
0
19
Order By: Relevance
“…In this study, the project-based learning model has a positive effect on the formation of students' self-concepts. The results of this study provide the latest findings which in the results of previous studies put forward by (Cahyani & Akmal, 2017) that spirituality has a positive influence on the resilience of the final students, it turns out that the communication and creativity of lecturers in learning are also able to have a positive influence on student resilience.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, the project-based learning model has a positive effect on the formation of students' self-concepts. The results of this study provide the latest findings which in the results of previous studies put forward by (Cahyani & Akmal, 2017) that spirituality has a positive influence on the resilience of the final students, it turns out that the communication and creativity of lecturers in learning are also able to have a positive influence on student resilience.…”
Section: Discussionsupporting
confidence: 71%
“…Cavis (2015) states that spiritual and religious meanings can help individuals who experience difficult times to develop in a healing process. Research conducted by Cahyani and Akmal (2017) also showed that spirituality, which is interpreted as a person's struggle to achieve goals and undergo connectedness with oneself, other people, and transcendent forces, plays a significant role in resilience. The emergence of the spirituality theme could be associated with the locations where the participants were taken, namely religion-based hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Sama halnya dengan yang terjadi pada resiliensi mahasiswa, demografi pun dapat mempengaruhi tingkat resiliensi mahasiswa, sehingga tingkatan resiliensi yang dimiliki pun akan bervariasi. Adapun karakteristik-karakteristik demografi yang pernah diteliti pada resiliensi mahasiswa diantaranya adalah jenis kelamin, budaya, dan agama (Amelia, Asni & Chairilsyah, 2014;Azzahra, 2017;Cahyani & Akmal, 2017;Mufidah, 2017;Prihartono, Sutini, & Widianti, 2018;Roellyana & Listiyandini, 2016;Willda, Nazriati, & Firdaus, 2016) Pada penelitianpenelitian tersebut ditunjukkan adanya salah satu kelompok berdasarkan karakteristik demografi tersebut yang lebih resilien.…”
Section: Pendahuluanunclassified
“…Dalam hal ini berupa kepercayaan pada Tuhan atau nasib yang dengan proses perenungan dan adaptasinya dalam menghadapi kesulitan akan memberikan pemikiran positif dan membangkitkan motivasi untuk mencari solusi (Connor & Davidson, 2003). Hal itu pun dapat terjadi pada mahasiswa keperawatan yang sedang mengerjakan skripsi, di mana keterlibatan agama atau spiritualitas pada mahasiswa yang sedang mengerjakan skripsi menunjukkan hasil yang positif (Cahyani & Akmal, 2017;Prihartono et al, 2018;Willda et al, 2016). Dengan demikian, mahasiswa keperawatan yang sedang mengerjakan dan menemui kesulitan dalam prosesnya sangat mungkin mengandalkan kepercayaan pada Tuhannya untuk merubah nasibnya lebih baik.…”
Section: Mahasiswaunclassified